2022
DOI: 10.1007/s10447-022-09483-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Experiences of People who Engage with Pro-eating Disorder Online Media: A Qualitative Inquiry

Abstract: The harmful consequences of eating disorders can impact an individual’s physical, emotional, and psychosocial wellness. However, these consequences may be exacerbated by the use of pro-eating disorder online media. In this study, we used a hermeneutic phenomenological qualitative inquiry to explore the experiences of an international sample of adults engaging with pro-eating disorder online media. Analysis revealed themes and subthemes and provided context for meaning(s) individuals experience when engaging in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In addition to the evaluation of pro-ED websites, the search identified several studies where qualitative interviews were conducted with website users (n = 11). Many pro-ED site users reported that use of the sites increased competitive behaviour and led to higher rates of ED symptomology and DEB among users (Csipke & Horne, 2007;Dashow, 2022;Davis, 2010;Firkins et al, 2019;Gale et al, 2016;Logrieco et al, 2021;Mincey, 2019;Raulli, 2018;Rich, 2006;Telford, 2012;Yeshua-Katz & Martins, 2013). For example, Logrieco et al (2021) interviewed TikTok pro-ED users who try to 'prove they are in the worst condition by showing the numbers, calories, and parameters of "being really sick"' (p. 3).…”
Section: Pro-ed Communitiesmentioning
confidence: 99%
“…In addition to the evaluation of pro-ED websites, the search identified several studies where qualitative interviews were conducted with website users (n = 11). Many pro-ED site users reported that use of the sites increased competitive behaviour and led to higher rates of ED symptomology and DEB among users (Csipke & Horne, 2007;Dashow, 2022;Davis, 2010;Firkins et al, 2019;Gale et al, 2016;Logrieco et al, 2021;Mincey, 2019;Raulli, 2018;Rich, 2006;Telford, 2012;Yeshua-Katz & Martins, 2013). For example, Logrieco et al (2021) interviewed TikTok pro-ED users who try to 'prove they are in the worst condition by showing the numbers, calories, and parameters of "being really sick"' (p. 3).…”
Section: Pro-ed Communitiesmentioning
confidence: 99%